Final answer:
To solve the equation 9(w – 4) – 7w = 5(3w – 2), distribute the numbers on both sides, combine like terms, move all the w terms to one side, divide both sides by -13, and solve for w. The solution is w = -2.
Step-by-step explanation:
To solve the equation 9(w – 4) – 7w = 5(3w – 2), we need to distribute the numbers on both sides and combine like terms. Here's the step-by-step solution:
- Distribute 9 to w and 4: 9w - 36 - 7w = 15w - 10
- Combine like terms: 2w - 36 = 15w - 10
- Move all the w terms to one side: 2w - 15w = 36 - 10
- Combine like terms: -13w = 26
- Divide both sides by -13 to solve for w: w = -2
Therefore, the solution to the equation is w = -2.